Parâmetros nutricionais, morfofisiológicos e fitodisponibilidade de metais nas culturas de crambe e trigo cultivadas em solos contaminados - Sousa, Ricardo Felipe Braga de (2015)
This paper proposes to evaluate the development of crambe and wheat plants cultivated in soil contaminated with levels of Cd and Pb. The soils were contaminated with metals using the CdCl2 and PbCl2H2O salts in five doses based on investigation values (IV) of Resolution #420 of CONAMA (dose 1 - existing value in the soil; dose 2 - half of the IV, dose 3 - IV; dose 4 - three times the IV and dose 5 - ten times the IV) resulting in 0; 1.5; 3; 9 and 30 mg kg-1 for Cd and 33; 90; 180; 540 and 1800 mg kg-1 to Pb prior to sowing. The development of the crops were evaluated, as well as gas exchange during vegetative and reproductive period, determining the parameters related to gas exchange. During flowering were determining plant nutrient composition of the N, P, K, Ca, Mg, Cu, Zn, Fe, Mn, besides of Cd and Pb. At the end of the cycle production components were quantified for both cultures. Subsequent to this, the plants were cut in plant parts and the bioavailability of metals in their tissues were determinate. In plants of crambe the soil contamination with Cd and Pb reduced photosynthesis, increased breathing also interferes negatively on mineral nutrition and productivity in general, the Cd s had a higher bioavailability when compared with Pb, being found in all plant parts of crambe from 1.5 mg kg-1 of Cd in the soil, Pb was retained only in the roots, not being translocated to the shoot. In wheat, according to the results, the contamination by Cd and Pb does not interfere with gas exchange, but negatively affects the development, mineral nutrition, roots and productivity of wheat plants. In plant tissue, Pb was less mobile than Cd, and accumulated in lower concentrations on, but from the VI's, both metals were found in the whole plant. Thus, although acceptable results, it is concluded that it is necessary more studies to be considered the use these plants in contaminated soil as production alternatives